1963
DOI: 10.1039/tf9635901026
|View full text |Cite
|
Sign up to set email alerts
|

Raman intensities. Part 9.—Vibrational intensities for spherically symmetric modes of CH4, CD4, CF4, SiF4, SF6, SeF6and TeF6

Abstract: Measurements of the vibrationalRaman intensities for the vl(u1) modes of C D 4 , CF4, SiF4, SF6, SeF6 and TeF6 dl in the gaseous state relative to the VI (UI ) mode of c& are reported. Values of derived bond polarizabilities are calculated and discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1967
1967
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…They are gathered in Table VI. The value of ∂ ᾱ/∂q 1 is known to a good accuracy both experimentally 63 and numerically (on the basis of second-order Møller-Plesset perturbation theory) 19 but given the poor accuracy of k 155 , the ∂ 2 ᾱ/∂q 2 5 values are given to three decimal places.…”
Section: A Derivativesmentioning
confidence: 99%
“…They are gathered in Table VI. The value of ∂ ᾱ/∂q 1 is known to a good accuracy both experimentally 63 and numerically (on the basis of second-order Møller-Plesset perturbation theory) 19 but given the poor accuracy of k 155 , the ∂ 2 ᾱ/∂q 2 5 values are given to three decimal places.…”
Section: A Derivativesmentioning
confidence: 99%
“…The Raman scattering cross-section ratio of CO 2 measured before is used to estimate the component concentrations of O 2 and SO 2 , which results in a relatively large discrepancy with the stated values in the reference gas samples. Long et al reported the relative Raman intensity of CF 4 (ν 1 , 909 cm –1 ) related to CH 4 (ν 1 , 2917 cm –1 ). Furthermore, considering the correction of the effect of the high-reflectivity mirror and using CO 2 as the internal standard gas, we gave an estimated content of CF 4 .…”
Section: Applicationsmentioning
confidence: 99%
“…While the expression for the isotropic invariant of the second dipole hyperpolarizability of N 2 given by Maroulis agrees with that reported in [7], in the case of SF 6 the two authors have reported two different expressions; however, both expressions lead to the same formal result when the molecules are treated as point-polarizable particles, which is the model used throughout this paper (see [8]). For the first polarizability derivative of SF 6 , the experimental value was taken [18], even though ab initio results for self-consistent field (SCF) or MP2 level are also available [16]. For the quadrupole polarizability derivative, the MP2 value of [16] was used.…”
Section: A Trace and Momentsmentioning
confidence: 99%